Sistem Monitoring Schedule Compliance untuk Pengendalian Shortage Material pada Proses Produksi Extruder - Daffa Aji Firmansyah; Priskila Christine Rahayu (Universitas Pelita Harapan, 2026)
Compliance schedule management for extruder machines in manufacturing environments is often still performed manually, leading to reporting delays, recording errors, and limited visibility of schedule adherence and material readiness. This study aims to develop a digital-based compliance schedule monitoring system to improve the effectiveness of production schedule control, material availability tracking, and detection of non-conforming schedules. The system was developed using the Rapid Application Development (RAD) approach, which includes requirement planning, system design (use case diagram, data flow diagram, and entity relationship diagram), prototype development, and implementation testing in an operational environment. The proposed system integrates production schedule data, material usage, material shortage information, and compliance status into a centralized dashboard displaying real-time performance and compliance indicators. Testing results show a significant reduction in monitoring time from 38.63 minutes in the manual system to 0.61 minutes using the proposed system, resulting in a time efficiency improvement of 98.42%. Furthermore, the system enhances information transparency, decision-making speed, and reporting accuracy. Therefore, the developed system is effective in supporting data-driven operational control in manufacturing production processes.